Change management - Lewin, David (Henry Stewart Talks, 2011)
Why change management is pervasive, Resistance, Ambidextrous organizations, Organizational evolution, Organizational alignment, Change drivers and traps, Organizational ambidexterity, Successful organizational change, Leading change, Errors in organizational change, Eight steps to successful organizational change
Reviewed at 2016/06/30